2017
DOI: 10.1155/2017/5651736
|View full text |Cite
|
Sign up to set email alerts
|

Variable Ratio Hydrostatic Transmission Simulator for Optimal Wind Power Drivetrains

Abstract: This work presents a hydromechanical transmission coupled to an electric AC motor and DC generator to simulate a wind power turbine drive train. The goal of this project was to demonstrate and simulate the ability of a hydrostatic variable ratio system to produce constant electric power at varying wind speeds. The experimental results show that the system can maintain a constant voltage when a 40% variation in input speed is produced. An accompanying computer simulation of the system was built and experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In 2015, Gu et al studied the same transmission system, shown as Figure 23, and studied the characteristics of the hydraulic system, and compared with the mechanical transmission system, the fully hydraulic wind turbine could effectively absorb the fluctuating load from the wind turbine rotor 101 . And it was testified in Garcia‐Bravo et al 102 that the VPFM has the ability of a hydrostatic variable ratio to produce constant electric power at varying wind speeds.…”
Section: The Hydraulic Technology Applications In Wind Turbinementioning
confidence: 99%
“…In 2015, Gu et al studied the same transmission system, shown as Figure 23, and studied the characteristics of the hydraulic system, and compared with the mechanical transmission system, the fully hydraulic wind turbine could effectively absorb the fluctuating load from the wind turbine rotor 101 . And it was testified in Garcia‐Bravo et al 102 that the VPFM has the ability of a hydrostatic variable ratio to produce constant electric power at varying wind speeds.…”
Section: The Hydraulic Technology Applications In Wind Turbinementioning
confidence: 99%
“…In general, properly designed hydromechanical transmissions proved themselves as reliable systems that perform robustly under sever industrial operating conditions. During the last few decades, many configurations of hydromechanical transmissions have been extensively investigated theoretically and experimentally in wind energy industry 28,32,37–45 . The main objective of the adoption of a hydromechanical transmission in wind turbine drivetrains is the elimination of the “unreliable” power conversion electronics.…”
Section: Introductionmentioning
confidence: 99%